Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
The theme of this number of PSYCHOLOGY IN SOCIETY (PINS) could be said to be related to an investigation of the psychology of the subaltern, and more especially in the southern African context, the racialised other. In many ways the oppressed have never had it so bad. The so-called revolutions of the late 1980s have wreaked more havoc than brought any significant material benefits. As certain hegemonic projects that contained the false unity in nation states have collapsed, the effects have not been the flowering of democratic freedoms and a disciplined and respectful politics of difference. Instead, we have witnessed some of the most savage onslaughts against ordinary people in their different struggles for freedom and dignity; from Sarajevo to Boipatong; from Los Angeles to Mogadishu; from Huambo to Baghdad. And yet the politics of the time seems to be a kind of transpolitics, to borrow a term of Baudrillard’s, a politics of global and international forces that leaves very little space and hope for the actions of ordinary citizens.